Feasability of a Frameless Brain Biopsy System for Companion Animals Using Cone-Beam CT-Based Automated Registration - Meneses, Felix; Maiolini, Arianna; Forterre, Franck; Oevermann, Anna; Schweizer-Gorgas, Daniela (Frontiers in Veterinary Science, 2022)
The aim of the present study was to evaluate the use of a novel intraoperative cone-beam computed tomography (CBCT)-based automated registration system for frameless stereotactic brain biopsy in companion animals. An experimental cadaveric study evaluated thalamic and piriform lobe target site needle placement error in three dogs and three cats without a history of intracranial disease. Diagnostic accuracy and diagnostic yield were prospectively evaluated in twenty-four client-owned dogs and four cats with intracranial disease. Twenty-one procedures were performed post mortem (eighteen dogs and three cats), and seven biopsy procedures were performed in alive patients (six dogs and one cat). Procedural duration was evaluated in ten post mortem and four living patients. Outcome was evaluated in six dogs and one cat. In dogs, the calculated median needle placement error was 1.8 mm (range 0.71 – 2.84 mm) and 1.53 mm (range 1.45 – 1.99 mm) for piriform lobe and thalamus target sites, respectively. In cats, the calculated median needle placement error was 0.79 mm (range 0.6 – 1.91 mm) for the piriform lobe target site and 1.29 mm (range 0.47 – 2.69 mm) for the thalamic target site. The diagnostic yield was 96.4% (95% CI 0.81 – 0.99), the diagnostic accuracy was 94.4% (95% CI 0.72 – 0.99). Median total procedural duration for post mortem biopsies was 57.5 minutes (range 41 - 69 minutes). Median total procedural duration for intra vitam biopsies was 122.5 minutes (range 103 - 136 minutes). Three dogs were discharged one day after biopsy and one dog after six days. Two dogs and one cat were euthanized 24 and 48 hours after biopsy. Intraoperative CBCT-based automated image registration for frameless stereotactic biopsies in companion animals is capable of providing diagnostic brain biopsy specimens independent of skull size and morphology with diagnostic yield and accuracy comparable to published values for diverse frameless and frame-based stereotaxy systems used in veterinary medicine. Duration of the procedure is not negatively affected and within the published range with other systems. Mobile intraoperative CBCT-based registration combined with neuronavigation delivers diagnostic brain biopsies in companion animals.